Impact of the REACH II and REACH VA dementia caregiver interventions on healthcare costs - Nichols, Linda O. (J Am Geriatr Soc, 2017)
OBJECTIVE: Examine caregiver and care recipient healthcare costs associated with caregivers’ participation in Resources for Enhancing Alzheimer’s Caregivers Health (REACH II or REACH VA) behavioral interventions to improve coping skills and care recipient management. DESIGN: RCT (REACH II); propensity-score matched, retrospective cohort study (REACH VA). SETTING: Five community sites (REACH II); 24 VA facilities (REACH VA). PARTICIPANTS: Care recipients with Alzheimer’s Disease and Related Dementias (ADRD) and their caregivers who participated in REACH II study (analysis sample of 110 caregivers and 197 care recipients); care recipients whose caregivers participated in REACH VA and a propensity matched control group (analysis sample of 491). MEASUREMENTS: Previously collected data plus Medicare expenditures (REACH II) and VA costs plus Medicare expenditures (REACH VA) RESULTS: There was no increase in VA or Medicare expenditures for care recipients or their caregivers who participated in either REACH intervention. For VA care recipients, REACH was associated with significantly lower total VA costs of care (33.6%). VA caregiver cost data was not available. CONCLUSION: In previous research, both REACH II and REACH VA have been shown to provide benefit for dementia caregivers at a cost of less than $5/day; however, concerns about additional healthcare costs may have hindered REACH’s widespread adoption. Neither REACH intervention was associated with additional healthcare costs for caregivers or patients; in fact, for VA patients, there were significantly lower healthcare costs. The VA costs savings may be related to the addition of a structured format for addressing the caregiver’s role in managing complex ADRD care to an existing, integrated care system. These findings suggest that behavioral interventions are a viable mechanism to support burdened dementia caregivers without additional healthcare costs.